1986
DOI: 10.1007/bf02343797
|View full text |Cite
|
Sign up to set email alerts
|

The energetics of endurance running

Abstract: Maximal O2 consumption (VO2max) and energy cost of running per unit distance (C) were determined on the treadmill in 36 male amateur runners (17 to 52 years) who had taken part in a marathon (42.195 km) or semi-marathon (21 km), their performance times varying from 1.49 to 226 and from 84 to 131 min, respectively. VO2max was significantly (2p less than 0.001) greater in the marathon runners (60.6 vs 52.1 ml . kg-1 . min-1) while C was the same in both groups (0.179 +/- 0.017, S.D., mlO2 . kg-1 . m-1 above rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
225
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(247 citation statements)
references
References 12 publications
17
225
0
5
Order By: Relevance
“…The energy cost of running on level and on positive gradients has been extensively investigated (1,2), and the place of Cr among ultra-endurance performance factors is still debated (3,4). According to (2) and (5) (2016) demonstrated that this statistical relationship could hide individual variations with a significant impact on the performance during mountain races (6) in a homogeneous group of high level mountain endurance runners.…”
Section: Introductionmentioning
confidence: 99%
“…The energy cost of running on level and on positive gradients has been extensively investigated (1,2), and the place of Cr among ultra-endurance performance factors is still debated (3,4). According to (2) and (5) (2016) demonstrated that this statistical relationship could hide individual variations with a significant impact on the performance during mountain races (6) in a homogeneous group of high level mountain endurance runners.…”
Section: Introductionmentioning
confidence: 99%
“…Variability in between-subject distance running performance is explained by three aerobic capacities: maximal oxygen uptake (V ・ O2max), lactate threshold (LT) intensity and running economy (RE) 1) . In particular, distance running performance has been observed to have a strong relation with the RE in well-trained runners 2) and highly trained athletes 3) .…”
Section: Introductionmentioning
confidence: 99%
“…several hours [22,23]) is undergoing unprecedented popularity. Additionally, the potential link with the energy cost of running [24,25] is a crucial factor of human running performance [26]; for moderate intensity Heise and Martin found an inverse relationship between aerobic demand and stiffness [25]. For severe intensity, Dalleau et al [24], Slawinski et al [20], and Rabita et al [19], confirmed that, during a constant-velocity, time-to-exhaustion run on track or treadmill, the same inverse relationship was observed.…”
mentioning
confidence: 81%